Nitrate transporters in leaves and their potential roles in foliar uptake of nitrogen dioxide - Hu, Yanbo; Fernandez, Victoria (Frontiers in Plant Science, 2014)
While plant roots are specialized organs for the uptake and transport of water and nutrients, the absorption of gaseous or liquid mineral elements by aerial plant parts has been recognized since more than one century. Nitrogen (N) is an essential macronutrient which generally absorbed either as nitrate (NO−3) or ammonium (NH+4) by plant roots. Gaseous nitrogen pollutants like N dioxide (NO2) can also be absorbed by plant surfaces and assimilated via the NO−3 assimilation pathway. The subsequent NO−3 flux may induce or repress the expression of various NO−3-responsive genes encoding for instance, the transmembrane transporters, NO−3/NO−2 (nitrite) reductase, or assimilatory enzymes involved in N metabolism. Based on the existing information, the aim of this review was to theoretically analyze the potential link between foliar NO2 absorption and N transport and metabolism. For such purpose, an overview of the state of knowledge on the NO−3 transporter genes identified in leaves or shoots of various species and their roles for NO−3 transport across the tonoplast and plasma membrane, in addition to the process of phloem loading is briefly provided. It is assumed that a NO2-induced accumulation of NO−3/NO−2 may alter the expression of such genes, hence linking transmembrane NO−3 transporters and foliar uptake of NO2. It is likely that NRT1/NRT2 gene expression and species-dependent apoplastic buffer capacity may be also related to the species-specific foliar NO2 uptake process. It is concluded that further work focusing on the expression of NRT1 (NRT1.1, NRT1.7, NRT1.11, and NRT1.12), NRT2 (NRT2.1, NRT2.4, and NRT2.5) and chloride channel family genes (CLCa and CLCd) may help us elucidate the physiological and metabolic response of plants fumigated with NO2.